The Artistic Image in COVID-19 poetry:A Comparative Study of Selected Models ofFeminine and Masculine Poetry (مجلة إحالات, 2026)
The poet is a creation of his environment, an expression thataccompanied the evolution of literarycriticism movement since ancient times. This notion emphasizes on the important impact of the environment on the poetic composition, considering pandemics as one of its environmental effects. Thus, it is incumbent upon literature, including poetry, to represent it, based on the emotions it leaves behind, which are difficult toovercome. The poets are inclined to evoke many artistic images to depict the duality of pain and hopethrough their lexical choices, structural techniques, and rhetorical expressions. This is appears in manycontemporary poetic experiences that sought to provide a vivid portrayal of what the pandemic, particularly COVID-19 and its impacts on individuals and society at large, undermining the globalized village that it strived to build, turning them into isolated communities preoccupied with their own affairs. Notably, on thepoetic level, the feminist poem relies on artistic images that intersect with those available in male poetry. Therefore, this research paper aims to elucidate these artistic images between the two experiences concerningnature, gender, and impact, relying on the tools of comparative study.